The effectiveness analysis of the university-business interaction institutional mechanism and recommendations for its improvement - Drakh, T.P.; Salzhanova, Z.A.; Vitrenko, A. (KSU Publ., 2020)
Object: The purpose of this study is to provide justification of Business Interaction Centers on the basis of organisational models, determine its functions, tasks and indicators for evaluating its work for different types of universities, taking into account business interests ensuring direct and most active participation of the business community in performance of educational, scientific and entrepreneurial functions of the university. Methods: The methods are content, comparative, retrospective types of analysis. Findings: The article includes the results of analysis of the effectiveness of university-business interaction in Kazakhstan, based on the Matrix of characteristics of the UBI institutional mechanism and the profile of an entrepreneurial university, which has found that formally all universities have required departments for interacting with business for entrepreneurial, educational and scientific activities, but the majority of the universities studied do not have a integrated center for interaction with business. Conclusions: Increasing the effectiveness of interaction with business, universities are required to make changes to their organizational structure and create the integrated unit for interaction – the Business Interaction Centre.
Жоғары оқу орындары мен бизнестің өзара əрекеттесу тетігін ұйымдастырудың тиімділігін талдау жəне оны жетілдіру бойынша ұсыныстар
Анализ эффективности организационного механизма взаимодействия вузов и бизнеса и рекомендации по его совершенствованию
Keywords: institutional mechanism; Business Interaction Centre; university-business interaction; entrepreneurial university; functions of Business Interaction Centre; forms of interaction; organizational model; organizational structure